Comparison of the Effectiveness of Mediation-Based Intervention and Behavioral Intervention on Teaching Organizational Skills in Students With Attention-Deficit/Hyperactivity Disorder - Hajinezhad, Zahra; Amin Yazdi, Sayed Amir; Kareshki, Hossein; Mashhadi, Ali (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The objective of this study was to compare the effectiveness of behavioral organizational skills training (OST) and mediated learning–based intervention in improving organizational skills among elementary school students with Attention-Deficit/Hyperactivity Disorder (ADHD).Methods and Materials: This study employed a quasi-experimental pretest–posttest design with a control group. The study population consisted of elementary school students aged 9 to 11 years diagnosed with ADHD during the 2023–2024 academic year in Mashhad. A total of 55 students and their mothers were initially recruited through voluntary sampling and randomly assigned to three groups: behavioral organizational skills training (OST), mediated learning–based organizational skills intervention, and a control group. Due to attrition and group size balancing, data from 45 participants (15 per group) were analyzed. The OST program was delivered in 16 group sessions, while the mediated learning intervention was conducted in 13 group sessions, both involving active parental participation. Data were collected using the SNAP-IV Parent Form to confirm ADHD symptoms and the Parent Version of the Children’s Organization, Planning, and Sequencing Scale (P-COSS) to assess organizational skills, including task tracking, materials management, time management, and task planning. Data were analyzed using multivariate and univariate analyses of covariance, controlling for pretest scores.Findings: Multivariate analysis of covariance revealed a significant overall difference between the combined posttest organizational skills scores of the experimental groups and the control group (p < .001). Univariate analyses indicated significant group differences in task tracking, materials management, time management, and task planning (all p < .001), with large effect sizes. Bonferroni post hoc comparisons showed that both intervention groups performed significantly better than the control group across all organizational skill components, while no significant differences were observed between the two intervention groups.Conclusion: Both behavioral organizational skills training and mediated learning–based intervention were equally effective in improving organizational skills in students with ADHD, suggesting that either approach can be selected based on contextual, familial, and educational considerations.